Learning Design Project Based Learning Based on Chemical Literacy whit the Theme of Electrolyte and Non-Electrolyte Solutions - Fhira Aulia Fitri; Eka Yusmaita (Entalpi Pendidikan Kimia, 2022)
In the 21st century, a learning design is needed that can increase the motivation and activeness of students in the learning process. The solution is to develop a project-based learning design based on chemical literacy. The purpose of this study was to develop and determine the level of validity of the project based learning design based on chemical literacy with the theme of electrolyte and non-electrolyte solutions. The type of research is educational design research using the plomp model and data processing using the Aiken's V formula. The validity test for the learning design is carried out by distributing instruments in the form of content validity questionnaires and construct validity questionnaires which are categorized as valid.